2014
DOI: 10.1371/journal.pone.0104704
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Randomized-Controlled Trial of a Classroom-Based Drama Workshop Program to Improve Mental Health Outcomes among Immigrant and Refugee Youth in Special Classes

Abstract: ObjectivesThe aim of this cluster randomized trial was to evaluate the effectiveness of a school-based theatre intervention program for immigrant and refugee youth in special classes for improving mental health and academic outcomes. The primary hypothesis was that students in the theatre intervention group would report a greater reduction in impairment from symptoms compared to students in the control and tutoring groups.MethodsSpecial classrooms in five multiethnic high schools were randomly assigned to thea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 32 publications
0
35
0
6
Order By: Relevance
“…However, S‐SDQ impact or impairment ratings (viewed as primary outcomes) decreased significantly for Rousseau et al () and Rousseau et al (), and for first‐generation but not second‐generation youth (Rousseau et al, ). Control groups' S‐SDQ impact and T‐SDQ TDSs increased significantly (Rousseau et al, ; Rousseau et al, ), again possibly due to non‐intervention.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…However, S‐SDQ impact or impairment ratings (viewed as primary outcomes) decreased significantly for Rousseau et al () and Rousseau et al (), and for first‐generation but not second‐generation youth (Rousseau et al, ). Control groups' S‐SDQ impact and T‐SDQ TDSs increased significantly (Rousseau et al, ; Rousseau et al, ), again possibly due to non‐intervention.…”
Section: Resultsmentioning
confidence: 90%
“…Three studies evaluated classroom‐based drama therapy workshops for refugee and immigrant youth in Canada (Rousseau, Armand, Laurin‐Lamothe, Gauthier, & Saboundjian, ; Rousseau et al, ; Rousseau et al, ). Students completed S‐SDQs in French, English, or students' (unspecified) native languages, supported by multilingual project staff (Rousseau et al, ); with interviewers (Rousseau et al, ); or requested translated versions (Rousseau et al, ). The three studies found no significant decreases in S‐ and T‐SDQ TDSs (viewed as secondary global measures by Rousseau et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations